IV Paracetamol versus Oral Ibuprofen for Closure of Patent Ductus Arteriosus in Preterm Neonates Admitted To a Tertiary Care Centre in North Karnataka, India- A Randomized Control Trial - Siddu Charki; Trimal Kulkarni; Vijayakumar Biradar; M M Patil; S S Kalyanshettar (Wolters Kluwer Medknow Publications, 2020)
Background: Patent ductus arteriosus (PDA) is a common disease in premature neonates, which could occur in up to 50% of the VLBW neonates. PDA might induce hemodynamic and respiratory disorders and increase mortality and morbidity. This study aimed to compare the effectiveness of oral ibuprofen and a low dose of intravenous paracetamol in the management of PDA. Materials and Methods: This study was conducted in NICU of Shri B M Patil Medical College Hospital and Research Center, BLDE (DU), Vijayapura. Study Design: Randomized double-blind study. Study duration: 6 months. Inclusion Criteria: Preterm neonates with the gestational age of <34 weeks and weight of >1000 g with hemodynamically significant symptomatic PDA. Exclusion Criteria: Gestational age > 34 weeks, Birth weight < 1000g and life-threatening illness. In total, 60 preterm neonates were enrolled, 30 of whom received 15 mg/ kg/6 h of intravenous paracetamol for 3 days and 30 neonates received 10 mg/kg of oral ibuprofen on the 1st day and 5 mg/kg for the next 2 days and the results include vital signs and echocardiography findings were compared. Results: In the paracetamol and ibuprofen groups, 24 (80%) and 26 neonates (87%) responded (PDA closure rate) to the treatment, respectively (P = 0.58). Furthermore, paracetamol and ibuprofen have a similar effect on vital signs. Both drugs did not change in blood pressure, but they reduced the respiratory rate and heart rate after treatment. Conclusion: Low dose intravenous paracetamol compared to oral ibuprofen has equal effectiveness in the closure of PDA.